Parâmetros físico-hídricos, lixiviação de nutrientes e desenvolvimento do girassol (Helianthus annuus L) em argissolo amarelo tratado com biocarvão - Lima, Idamar da Silva (2016)
The use of biochar in soil has been reported in countries like Japan and the United States, where the product already has reached commercial scale. The benefits of biochar go beyond improving the physical, chemical and biological soil properties, they involve regional and global environmental aspects, such as carbon sequestration in the soil and the efficient disposal of solid organic waste. This is because its resistant and recalcitrant organic nature. Investigation on the effects of biochar in weathered tropical soils with low water and nutrient storage capacity, as in most Brazilian soils and in the State of Sergipe, it is necessary and may stimulate new sustainable management practices. Therefore, the present study evaluated the effect of differentes rates of application of coconut husk biochar, produced through slow pyrolysis process, in the growth and development of sunflower plants and, in some soil physical and chemical properties. Soil organic carbon storage and soil solution composition were also evalauted. The experiment was conducted under greenhouse conditions at the Federal University of Sergipe, campus of St. Christopher-SE, between the months of July and October 2015. The soil used in the study was the surface layer of an Yellow Ultisol. The experimental design was a randomized complete block with 6 treatments (biochar rates of application: 0, 2.5, 5, 10, 20 and 30t ha-1) and 5 replications. Sixty-two days after plant emergence (DAE), all plants were evaluated for plant height, stem diameter at 2 cm of the soil, number of fully expanded leaves, flower diameter, and plant biomass dry weight. Soil solution was collected after specific irrigation events at 6, 13 and 20 days after plant emergency, and analyzed for pH EC, concentrations of P, K, nitrate and ammonium.Seven and 78 days after the incorporation of biochar, soil samples were collected from each experimental pot and analyzed for chemical (pH, EC, P, and exchangeable K, Na, Al, Ca, Mg concentrations, and organic C) and physical (field capacity, permanent wilting point, total water availability, soil bulk density, macro and microporosity) attributes. The physical attributes were only evaluated after 78 days. The soil carbon storage at the end of the experiment was calculated according to the bulk density and depth of the soil sampling. Adding biochar resulted in an increase in the levels of P and K at a depth of 0-20 cm. The high concentration of K at the 20-40 cm layer indicated that the element was leached from the top layer. Soil EC in the soil solution increased at both soil layers indicating a restriction on the use of large amount of biochar. The presence of biochar in the soil, regardless of the rate of application, did not influence the growth and development of sunflower, which can be seen as a positive effect because it means that this type of biochar can be applied to the soil to store carbon without causing harm to the plants. Biochar reduced the soil bulk density and increased microporosity, and as a result, improved water retention in the soil in about 64% at the highest rate of application. Furthermore, the presence of biochar reduced soil acidity and the availability of Al, but increased the electrical conductivity and the concentration of exchangeable Na, both at the beginning and at the end of the experiment. There was no influence of biochar on exchangeable concentrations of Ca and Mg, but the concentrations of P and K responded positively to the rate of application in the begining of the experiment, when no chemical fertilizers had been added to the soil. A positive response was observed for the K concentration in the end of the experiment. Although the addition of biochar improved the physical and chemistry quality of the soil, its implementation should be well attended due to excessive changes in soil pH and EC, and increase in Na concentration.